(untitled) (Research, Society and Development, 2022)
Introduction: Depression, a disorder that affects twice as many women as men, is a worrying issue in Brazil that crosses the social context and the role attributed to women. Objectives: This is a quantitative study that aimed to analyze the mortality profile of women in Brazil as a result of a depressive condition. Methodology: A search was conducted in the Mortality Information System (MIS) and was analyzed according to the International Classification of Diseases (ICD-10) categories: recurrent depressive disorder and depressive episodes (F33 and F32), examining the data from gender, race, aging, and marital status. The Results: A registry of 2,892 deaths was obtained between the period 2015 to 2019, where about 60% are women. Among the women, the most affected are the elderly, non-white women (brown and black), and widowed and single women; married women have significant values, but not higher. Conclusions: A diversity of factors linked to the mortality profile of women as a result of a depressive condition, the overload attributed to women within marriage, the racial issue, aging, as well as widowhood. The indices point to Minas Gerais, São Paulo, Rio de Janeiro, and Bahia as the regions with the highest rates. Therefore, it is necessary to invest in the prevention and promotion of quality of life, a support network for women who go through a situation that is considered a risk factor for depression, especially in marginalized regions of the states mentioned.